Perbandingan ARMA dan Single Exponential Smoothing pada Peramalan Harga Ayam Broiler di Jawa Barat - Sabastya, Alfian; Simbolon, Ani Ngalemisa; Fatimatuzzuhra; Agustina, Neli (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2024)
Fluctuations in broiler chicken prices require farmers to predict prices to plan production and optimize business profits. This study aims to predict broiler chicken prices in West Java to help farmers plan their budgets and business income. This study compares the accuracy of the ARMA (Autoregressive Moving Average) model with the Single Exponential Smoothing method in predicting broiler chicken prices in the West Java region. The results show that the ARMA (0.1) model has the best performance with the smallest measurement error rate, namely MAPE 4.48, MSE 49.27, and RMSE 2427.38. The price prediction for January 2025 is 35,043.63. These results are expected to help farmers in budget planning and improve business efficiency.